A comparative clinical study of gallbladder tubular adenocarcinoma according to the grade of differentiation - Egawa, Naoto; Tu, Yuyang; Kamisawa, Terumi; Amemiya, Kozue; Tsuruta, Kouji; Okamoto, Atsutake; Funata, Nobuaki (Journal of gastroenterology, 2004)
We sought to elucidate differences in the clinical characteristics of gallbladder carcinoma according to the histological degree of glandular formation. The subjects consisted of 66 autopsy cases out of 331 patients admitted for gallbladder carcinoma between 1975 and 2000. After identifying 49 tubular adenocarcinoma cases, we arbitrarily divided them into two categories: a well-differentiated type (group W; n=41; well or moderately differentiated tubular adenocarcinoma), and a poorly differentiated type (group P, n=8). The clinical features of the groups were compared. No significant differences were found with regard to sex, age, or serum carcinoembryonic antigen (CEA) levels between the two groups. Moreover, no intergroup difference was found in either the time interval from the initial symptoms to admission, or the grade of tumor progression on admission. Although the frequency of liver metastases on admission was similar in both groups, the frequency at autopsy was significantly higher in group W than in group P (73% vs 25%; P <0.05). When survival was determined based on the duration after primary treatment, the longest and median periods were 48.7 months and 3.7 months, respectively, in group W, whereas none of the subjects in group P survived for over 2 months. This difference was statistically significant ( P <0.001). Hematogenous metastasis was more prominent in group W. Poorly differentiated tubular adenocarcinoma can be closely associated with a poor prognosis.